All boys aren't blue eaudiobook A memoir-manifesto. - Johnson, George M. (Macmillan Young Listeners, 2020)
This program is read by the author. In a series of personal essays, prominent journalist and LGBTQIA+ activist George M. Johnson's All Boys Aren't Blue explores their childhood, adolescence, and college years in New Jersey and Virginia. A New York Times Bestseller! Good Morning America, NBC Nightly News , Today Show , and MSNBC feature stories From the memories of getting his teeth kicked out by bullies at age five, to flea marketing with his loving grandmother, to his first sexual relationships, this young-adult memoir weaves together the trials and triumphs faced by Black queer boys. Both a primer for teens eager to be allies as well as a reassuring testimony for young queer men of color, All Boys Aren't Blue covers topics such as gender identity, toxic masculinity, brotherhood, family, structural marginalization, consent, and Black joy. Johnson's emotionally frank style of writing will appeal directly to young adults. (Johnson used he/him pronouns at the time of publication.) Velshi Banned Book Club Indie Bestseller Teen Vogue Recommended Read Buzzfeed Recommended Read People Magazine Best Book of the Summer A New York Library Best Book of 2020 A Chicago Public Library Best Book of 2020 ... and more! A Macmillan Audio production from Farrar, Straus and Giroux